A Curious Diagnosis Causing Unilateral Proptosis : A Case Report : What started as a bizarre complaint leads to an unsuspected diagnosis - Banister, Elyse (Canadian Journal of Optometry, 2023)
Background: Sphenoid wing meningioma is one of the most common extraconal tumors and can present in various ways. Meningioma’s tend to affect females more than males and tend to be over the age of 50. Sphenoid wing meningiomas do not usually need treatment, unless the optic nerve is threatened or rapidly invading surrounding brain structures. Case Report: A 48-yr old female presented with a longstanding complaint of headaches for past 3-4 months and a new complaint of ocular pain and yellow fluid packet in the left eye for the past month. Ocular exam revealed unilateral proptosis of the left eye. Neuroimaging revealed a left sphenoid wing meningioma. Referral to neurology resulted in removal of the intracranial lesion. The patient is currently being followed with yearly exam with neurology and optometry. The case report includes discussion on pathogenesis, prognosis and management of sphenoid meningiomas. Conclusion: Meningiomas are considered to be benign lesions of the brain. They were once believed to be caused by hormonal variation , due to the predilection to be mostly for women. It is now believed the culprit lies in the genetic disorder Neurofibromatosis type 2 and monosomy 22, as most meningiomas have been found to contain one or both mutations. Management includes yearly eye examination once stability of tumor resection has been established by neurology and continuing with neurology for annual MRI or CT scans.